STRATEGI MANAJEMEN PENDIDIKAN UNTUK MENINGKATKAN EFEKTIVITAS PROSES PEMBELAJARAN DI ERA DIGITAL - Maulida Rizka Yulianti; Meidina Larasati; Shelina Nilawati; Arita Marini (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2024)
The purpose of the study is to investigate how Management of Islamic Education (MPI) can improve the quality of learning in the digital era by optimizing the use of technology in learning and ensuring the application of positive values in the use of digital technology for the character of the younger generation. This is expected to make a significant contribution in the development of relevant and effective MPI to improve the quality of Islamic education in accordance with the demands of the times. The research method used is a literature study, where data is obtained through critical and in-depth analysis of various literature sources such as books, journals, and previous research to support research propositions and ideas. The results show that the use of technology in learning increases the accessibility, flexibility and interactivity of learning. Appropriate education management strategies, such as digital competency development for educators and partnerships between stakeholders, are needed to improve the effectiveness of learning in the digital era with concrete steps such as the provision of relevant infrastructure and curriculum.